Carbon fertilization of autochthonous production in karst surface waters and its role in carbon reduction and eutrophication mitigation—a nature-based solution (NbS) - Shao, Mingyu; Liu, Zaihua; Zeng, Sibo; Sun, Hailong; He, Haibo (Frontiers in Geochemistry, 2025)
As an important link in the global carbon cycle, the carbon sink function of inland water bodies has attracted much attention in recent years. In particular, the autochthonous production (AP) associated with aquatic photosynthesis in karst surface waters converts dissolved inorganic carbon (DIC) into autochthonous organic carbon (the “carbon sink by carbonate weathering coupled with aquatic photosynthesis, CCW”), which is the key to the formation of a long-term stable carbonate weathering sink. After nearly 20 years of development, the “CCW” theory, as a nature-based solution, has been found to have a win-win mechanism of sink enhancement and water environment improvement. The specific mechanism is that dissolved aquatic CO2 (CO2(aq)) fertilization can effectively alleviate the carbon limitation of the water body, promote the productivity of the water body to achieve carbon sink enhancement, and achieve the inhibition of eutrophication through the modification of the biological structure and the co-precipitation of CaCO3 and phosphorus to enhance the efficiency of phosphorus removal. In conclusion, the carbon fertilization of AP effect in karst surface water bodies has a huge carbon storage capacity and water environment improvement capacity. This paper reviews the detailed process of AP effect in karst surface waters, especially about the possibility of carbon sink and eutrophication mitigation win-win by CO2 fertilization of water bodies and its mechanism of action. Finally, based on the current research gaps, we outline the future research priorities of AP in karst surface water bodies. This study will provide new theoretical basis and scientific support for the regulation of carbon sinks and water quality safety in karst surface waters.